The Role Of Chitosan And Whey Powder In Calcium, Magnesium And Phosphorus Metabolism And Their Effect On Bone Tissue Metabolism In Broiler Chicks (Eurasian Research Bulletin, 2026)
This scientific article provides an expanded discussion of the effects of chitosan and whey powder on mineral metabolism in broiler chicks, with particular emphasis on the biological utilization of calcium, magnesium, and phosphorus and their contribution to bone tissue metabolism. Based on scientific literature, experimental findings, and veterinary biochemical observations, the paper analyzes chitosan’s ability to form complexes with mineral ions, its involvement in osteogenesis, and the mechanisms through which it enhances bone matrix formation and mineralization. It is also substantiated that combining chitosan with whey powder strengthens the osteogenic effect through improved nutrient availability and supportive bioactive components. The reported outcomes indicate improved bone density and mechanical strength parameters in broiler chicks receiving rations supplemented with chitosan and whey powder.